Loss in Executive Functioning Best Explains Changes in Pain Responsiveness in Patients with Dementia-Related Cognitive Decline. (14th December 2015) - Kunz, Miriam; Mylius, Veit; Schepelmann, Karsten; Lautenbacher, Stefan
Abstract : There is ample evidence that dementia changes the processing of pain. However, it is not known whether this change in pain processing is related to the general decline in cognitive functioning or whether it may be related to specific domains of cognitive functioning. With the present study we tried to answer this question. We assessed different cognitive domains (orientation, memory, abstract thinking/executive function, aphasia and apraxia, and information processing speed) in 70 older patients with cognitive impairment (mild cognitive impairment up to moderate degrees of dementia). Pain responsiveness was assessed by measuring the nociceptive flexion reflex (NFR) threshold and facial responses to noxious electrical stimulation. Using regression analyses, we assessed which domain of cognitive functioning best predicted variance in pain responsiveness. Variance in pain responsiveness (NFR and facial expressions) was best explained by those items assessing executive functioning even when controlling for overall cognitive performance and memory functioning. The close association between executive functioning and pain responsiveness suggests that dementia-related neurodegeneration in prefrontal areas might result not only in reduced executive functioning but also in a loss of pain inhibitory potency, rendering the patient more vulnerable to pain. Our findings also suggest that pain assessment in dementia should be regularly completed by tests of cognitive functions.